Analysis of clinical profile and prescription pattern of malaria in a tertiary care hospital in Karnataka, India - N., Raghu Murthy; Rai, Seema (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Malaria is one of the leading causes of morbidity and mortality in developing countries like India. Plasmodium falciparum and Plasmodium vivax are the commonest species implicated for an increased incidence of malaria in India. The pattern of disease, signs, and symptoms vary from place to place, region to region due to demographic variations. The current study was undertaken to study the differences in the clinical profile of malaria, particularly signs and symptoms, complications and response to treatment in malaria. Methods: A retrospective, single center, surveillance study was carried out at a tertiary health care center in Mangalore. All patients aged above 18 years diagnosed as malaria by peripheral smear method and rapid diagnostic tests were included in the study. The clinical features, complications, and response to treatment were noted. Results: Fifty eight patients diagnosed as malaria were included in the study. Compared to other studies and nationwide incidences, here P. vivax emerged as the leading cause of malaria. All patients presented with fever varying from 3-20 days. About 30 patients complained of headache and 21 patients presented with malaise. In about 6 patient’s complications were seen. Majority of patients received artemisinin derivatives followed by chloroquine for treatment of malaria Conclusions: Previous thinking that complications are only seen with P. falciparum has to be changed. Now many complications, mild as well as severe type are seen in P. vivax malaria. Drug resistance is another global problem which needs to be tackled wisely by systematic usage of antimalarials.